Perbaikan Alur Aktivitas VA/VE (TMMIN Proposal) di PT Toyota Motor Manufacturing Indonesia - Jessica Pratiwi; Jani Rahardjo (Jurnal Titra, 2018)
VA/VE (Value Analysis/Value Engineering) is a cost reduction activity, embedded in ECI (Engineering Change Instruction) documents. VA/VE is done by eliminating or replacing parts to obtain lowest production cost, in accordance with the goals in Toyota Production System, which is the lowest cost with muda elimination. VA/VE idea is recorded in ECI documents that contain standard changes in parts usage. VA/VE ideas can come from TMMIN itself, suppliers, designers, and other Toyota affiliates countries. Problems occur in four VA/VE ECI in 2017 with the idea from TMMIN are costs rising and implementation delays. Problem analysis is done by using fishbone diagram tools. Improvements were made by adding activities, which are determination of implementation targets and export impact checks. Improvements are poured into DFD and Ji Kotei-Kanketsu for guidance of new activity. New activities need to be controlled and reviewed on a regular basis for continuous improvement in accordance with the Toyota Way's philosophy. The impact of improvement is expected to eliminate waste defect and delay, and prevent the occurrence of rework costs Rp38,568,000.00 per ECI (not including the opportunity loss to implement the cost reduction).